Clinical Impact of Muscle Quantity and Quality in Colorectal Cancer Patients: A Propensity Score Matching Analysis. Issue 8 (15th May 2018) - Okugawa, Yoshinaga; Toiyama, Yuji; Yamamoto, Akira; Shigemori, Tsunehiko; Yin, Chengzeng; Narumi, Aya; Omura, Yusuke; Ide, Shozo; Kitajima, Takahito; Fujikawa, Hiroyuki; Yasuda, Hiromi; Hiro, Junichiro; et al.
Abstract: Background: Sarcopenia is defined as the loss of skeletal muscle mass, accompanied by decreased muscle strength, and consists of myopenia and myosteatosis. Recent evidence has suggested the predictive value of sarcopenia for the risk of perioperative and oncological outcomes in various malignancies. The aim of this study was to clarify the clinical impact of myopenia and myosteatosis in colorectal cancer (CRC) patients. Methods: We analyzed the preoperative psoas muscle mass index and intramuscular adipose tissue content using preoperative computed tomography images from 308 CRC patients using statistical methods. Results: Despite no significant correlation between myosteatosis and prognosis, preoperative myopenia significantly correlated with clinicopathological factors for disease development, including advanced tumor depth ( P = 0.009), presence of lymphatic vessel invasion ( P = 0.006), distant metastasis ( P = 0.0007), and advanced stage classification ( P = 0.013). Presence of preoperative myopenia was an independent prognostic factor for both cancer‐specific survival (hazard ratio [HR]: 2.75, 95% confidence interval [CI]: 1.5–5.05, P = 0.001) and disease‐free survival (HR: 3.15, 95% CI: 1.8–5.51, P = 0.0001), and was an independent risk factor for postoperative infectious complications in CRC patients (odds ratio: 2.03, 95% CI:1.17–3.55, P = 0.013). Furthermore, these findings were successfully validated using propensity score matching analysis. Conclusions: Preoperative myopenia could be useful for perioperative management, and quantification of preoperative skeletal muscle mass could identify patients as a high risk for perioperative and oncological outcomes in CRC patients.